A method for preparing textured copper by directional control of graphene

CN122879671APending Publication Date: 2026-10-09ANHUI NONFERROUS METAL NEW MATERIALS RESEARCH INSTITUTE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611257934.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0006]针对现有技术的不足,本发明提供了一种石墨烯定向控制制备织构铜的方法,具备石墨烯诱导铜晶粒沿(111)面高度择优取向生长、晶界密度显著降低等优点,解决了传统多晶铜因晶界随机分布导致电子散射严重的问题

Benefits of technology

1、该石墨烯定向控制制备织构铜的方法,利用石墨烯与铜晶格的高度匹配性,成功诱导铜晶粒沿(111)面择优取向生长,制备出致密的(111)强织构铜材料,通过大幅减少晶界数量并降低电子散射,该材料有效突破了多晶铜的导电极限,其电导率可达103%IACS以上,接近单晶铜水平,解决了传统多晶铜导电性能受限的技术难题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879671A_ABST
    Figure CN122879671A_ABST
Patent Text Reader

Abstract

The application relates to a method for preparing textured copper by graphene directional control, and relates to the field of metal matrix composites, and comprises the following steps: 1) substrate preparation; 2) graphene induced growth; and 3) texture growth. The method for preparing textured copper by graphene directional control successfully induces copper grains to grow along the (111) plane preferential orientation by using the high matching property of graphene and copper lattices, and prepares dense (111) strong texture copper material. By greatly reducing the number of grain boundaries and reducing electron scattering, the material effectively breaks through the conductivity limit of polycrystalline copper, and the conductivity can reach more than 103% IACS, close to the level of single crystal copper, solves the problem that the conductivity of traditional polycrystalline copper is limited, the process flow is simple, the controllability is strong, and the method is easy to realize large-scale production. The obtained textured copper material not only has excellent electrical properties, but also has good mechanical strength, and can meet the strict requirements of high-end fields such as power transmission, electronic packaging and aerospace for high-conductivity and high-performance copper materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal matrix composites, specifically to a method for the directional controlled preparation of textured copper using graphene. Background Technology

[0002] Conductive materials are the most important material basis of modern power technology. Developing high conductivity materials is an important technical means to achieve energy conservation in the power industry and a requirement for the performance development of power equipment. Due to its good conductivity and low price, copper-based materials have always been the main conductive materials, and there is a wide demand for them in fields such as power transmission, transportation, industrial equipment and electronic information. In recent years, with the increasingly severe energy and environmental problems and the development of high technology, higher requirements have been put forward for the conductivity of copper-based materials. Developing ultra-high conductivity copper-based materials with conductivity significantly exceeding that of pure copper has important economic value and practical significance.

[0003] In 1913, the International Organization for Standardization (ISO) adopted annealed copper wire with a density of 8.89 g / cm³, a length of 1 m, a weight of 1 g, and a resistance of 0.15328 ohms as the measurement standard. At 20°C, the conductivity of this annealed copper wire, 58.0 × 10⁶ S / m, was defined as 100% IACS (International Standard for Annealed Copper). The conductivity (%IACS) of any other material can be calculated using the following formula: Conductivity (%IACS) = 0.017241 / ρ * 100%. Traditional polycrystalline copper has numerous grain boundaries, which scatter electrons, limiting... Further improvements in its conductivity have been achieved. Currently, the highest conductivity of polycrystalline copper is only 103% IACS, while single-crystal copper conductors with higher conductivity can approach that of silver (approximately 109% IACS). However, single-crystal copper is difficult to prepare and is expensive. Theoretical studies have shown that copper with specific crystallographic textures (such as (111) or (100) crystal plane orientations) can significantly reduce electron scattering due to reduced grain boundaries or consistent orientation, thereby achieving conductivity exceeding that of ordinary pure copper. Therefore, preparing copper materials with strong textures has become a key way to improve its performance.

[0004] In the existing technology, the methods for preparing textured copper mainly include physical or chemical vapor deposition, large deformation processing combined with recrystallization annealing, etc. However, these methods often have limitations such as complex processes, high equipment requirements, or strict requirements on the texture of the original materials. For example, although single-crystal copper foil can be obtained by temperature gradient annealing, the process control requirements are extremely high.

[0005] Graphene is ultrathin, ultralight, ultra-high strength, ultra-strong conductivity, excellent room temperature thermal conductivity and light transmittance, almost completely transparent, structurally stable, and has a wide range of applications and huge development prospects. It is a key material for promoting technological development. As a two-dimensional material with ultra-high carrier mobility, graphene has been used to enhance the conductivity of copper-based composite materials. Studies have shown that the (111) crystal plane of copper and the hexagonal structure of graphene have excellent lattice matching (lattice mismatch of only 3%-4%). ​​This strong interaction can not only induce orientation reorganization of the copper substrate during growth, but also provide an ideal template for the epitaxial growth of graphene, thereby realizing the texturing of the copper matrix in the composite material. Therefore, if the growth of graphene during CVD can be used to induce and control the texturing of the copper matrix, it will be a very promising technical route. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides a method for the directional control of graphene to prepare textured copper, which has the advantages of graphene-induced copper grains growing with highly preferred orientation along the (111) plane and significantly reduced grain boundary density, thus solving the problem of severe electron scattering caused by the random distribution of grain boundaries in traditional polycrystalline copper.

[0007] To achieve the above objectives, the present invention provides the following technical solution: A method for directionally controlled preparation of textured copper using graphene includes the following steps: 1) Substrate preparation: The copper foil is cleaned and dried to remove surface oil and oxides; 2) Graphene-induced growth: The treated copper foil is placed in an atmosphere tube furnace and heated to a predetermined temperature under a protective atmosphere; carbon source gas and auxiliary gas are introduced to carry out chemical vapor deposition reaction. During the reaction, the nucleation density, growth rate and coverage area of ​​graphene are precisely controlled by controlling parameters such as the proportion of carbon source gas, reaction time, system pressure and oxygen content, so that the polycrystalline copper foil (111) crystal plane can grow initially and form a textured growth template. 3) Texture growth: The single-layer copper-graphene composite material obtained in step 2) is stacked and hot-pressed under vacuum or protective atmosphere to achieve metallurgical bonding between layers. During the hot pressing process, the hexagonal structure of graphene will stabilize the (111) crystal plane. Its strong interfacial coupling with the copper matrix induces the copper grains to undergo directional recrystallization, causing other crystal planes of the polycrystalline copper foil to transform into the (111) crystal plane during the recrystallization process, forming a copper-graphene composite structure with strong (111) texture, and finally obtaining a dense bulk textured copper material with strong (111) texture.

[0008] Furthermore, the material grains exhibit a preferred orientation during the preparation process.

[0009] Furthermore, in step 2), the nucleation density and grain size of graphene are controlled by controlling the CH4 ratio and reaction time, thereby reducing the hot pressing conditions.

[0010] Furthermore, in step 3), the hot pressing temperature is 600℃-950℃, the pressure is 30-80MPa, and the holding time is 30-120min.

[0011] Furthermore, in step 2), the temperature of chemical vapor deposition is 900℃-1050℃, the carbon source gas is methane (CH4), and its flow rate accounts for 0.1%-5% of the total gas flow rate.

[0012] Furthermore, in step 2), a trace amount of oxygen or an oxygen-containing precursor is introduced while the carbon source gas is introduced, in order to regulate the interaction between the graphene edge and the copper substrate and promote the single-orientation growth of graphene.

[0013] Furthermore, in step 2), the protective atmosphere is a mixture of argon (Ar) and hydrogen (H2), wherein the hydrogen flow rate is 50 ml / min and the argon flow rate is 200 ml / min.

[0014] Furthermore, the preferred temperature for hot pressing sintering is 650℃-850℃, the pressure is 50MPa, and the holding time is 60min.

[0015] Furthermore, in the X-ray diffraction (XRD) pattern of textured copper materials with preferred orientation, the diffraction peak intensity of the copper (111) crystal plane is higher than that of the standard polycrystalline copper powder diffraction pattern, and electron backscatter diffraction shows that the grain orientation is highly consistent.

[0016] Compared with the prior art, the technical solution of this application has the following beneficial effects: 1. The method for preparing textured copper by directional control of graphene utilizes the high matching between graphene and copper lattice to successfully induce copper grains to grow along the (111) plane in a preferred orientation, thus preparing a dense (111) strongly textured copper material. By significantly reducing the number of grain boundaries and reducing electron scattering, this material effectively breaks through the conductivity limit of polycrystalline copper, and its conductivity can reach more than 103% IACS, which is close to the level of single-crystal copper, thus solving the technical problem of limited conductivity of traditional polycrystalline copper.

[0017] 2. The method for directional control of graphene to prepare textured copper is simple in process, highly controllable in parameters, and easy to achieve large-scale production. The resulting textured copper material not only has excellent electrical properties, but also good mechanical strength, which can meet the stringent requirements of high-conductivity and high-performance copper materials in high-end fields such as power transmission, electronic packaging and aerospace. It has extremely high practical value and promotion potential. Attached Figure Description

[0018] Figure 1 Raman plots of copper-graphene prepared at different methane flow rates according to this invention; Figure 2 The XRD diffraction patterns of textured copper prepared at different hot-pressing temperatures in the embodiments of the present invention are shown below. Figure 3 The images show the EBSD orientation patterns of textured copper prepared at different hot-pressing temperatures in this invention. Detailed Implementation

[0019] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0020] Example 1 Please see Figure 1-3 This embodiment describes a method for the directional controlled preparation of textured copper using graphene, comprising the following steps: (1) Cut commercial pure copper foil into the required size, and ultrasonically clean it in acetone, alcohol and deionized water for 10 minutes in sequence, and then dry it with nitrogen for later use.

[0021] (2) Place the cleaned copper foil in a tube furnace, evacuate it, and then introduce a mixture of Ar and H2 gas (H2 flow rate 50 ml / min, Ar flow rate 200 ml / min). Proceed to 1000℃ within 40 minutes. Hold at this temperature for 30 minutes for annealing.

[0022] (3) After annealing, CH4 gas (flow rate 10 ml / min) was introduced, and a trace amount of O2 (flow rate 0.5 ml / min) was introduced. The reaction time was 40 minutes. Subsequently, the mixture was naturally cooled to room temperature under Ar atmosphere protection to obtain a single-layer copper-graphene composite material. During this stage, the preferential growth of graphene induced the formation of a strong (111) texture in the copper matrix.

[0023] (4) Stack the single-layer composite materials prepared in step 3) neatly and place them in a hot press mold. Put the mold into a vacuum hot press furnace and evacuate it to below 10-3 Pa. Heat it to 750℃ and apply a pressure of 50 MPa at the same time, and keep it at that temperature for 1 hour. Then cool it to room temperature with the furnace and demold to obtain a bulk copper material with a high proportion of (111) texture.

[0024] Example 2 Please see Figure 1-3 This embodiment describes a method for the directional controlled preparation of textured copper using graphene, comprising the following steps: (1) Cut commercial pure copper foil into the required size, and ultrasonically clean it in acetone, alcohol and deionized water for 10 minutes in sequence, and then dry it with nitrogen for later use.

[0025] (2) Place the cleaned copper foil in a tube furnace, evacuate it, and then introduce a mixture of Ar and H2 gas (H2 flow rate 50 ml / min, Ar flow rate 200 ml / min). Proceed to 1000℃ within 40 minutes. Hold at this temperature for 30 minutes for annealing.

[0026] (3) After annealing, CH4 gas (flow rate 20 ml / min) was introduced, and a trace amount of O2 (flow rate 0.5 ml / min) was introduced. The reaction time was 40 minutes. Subsequently, the mixture was naturally cooled to room temperature under Ar atmosphere protection to obtain a single-layer copper-graphene composite material. During this stage, the preferential growth of graphene induced the formation of a strong (111) texture in the copper matrix.

[0027] (4) Stack the single-layer composite materials prepared in step 3) neatly and place them in a hot press mold. Put the mold into a vacuum hot press furnace and evacuate it to below 10-3 Pa. Heat it to 750℃ and apply a pressure of 50 MPa at the same time, and keep it at that temperature for 1 hour. Then cool it to room temperature with the furnace and demold to obtain a bulk copper material with a high proportion of (111) texture.

[0028] Example 3 Please see Figure 1-3 This embodiment describes a method for the directional controlled preparation of textured copper using graphene, comprising the following steps: (1) Cut commercial pure copper foil into the required size, and ultrasonically clean it in acetone, alcohol and deionized water for 10 minutes in sequence, and then dry it with nitrogen for later use.

[0029] (2) Place the cleaned copper foil in a tube furnace, evacuate it, and then introduce a mixture of Ar and H2 gas (H2 flow rate 50 ml / min, Ar flow rate 200 ml / min). Proceed to 1000℃ within 40 minutes. Hold at this temperature for 30 minutes for annealing.

[0030] (3) After annealing, CH4 gas (flow rate 20 ml / min) was introduced, and a trace amount of O2 (flow rate 0.5 ml / min) was introduced. The reaction time was 40 minutes. Subsequently, the mixture was naturally cooled to room temperature under Ar atmosphere protection to obtain a single-layer copper-graphene composite material. During this stage, the preferential growth of graphene induced the formation of a strong (111) texture in the copper matrix.

[0031] (4) Stack the single-layer composite materials prepared in step 3) neatly and place them in a hot press mold. Put the mold into a vacuum hot press furnace and evacuate it to below 10-3 Pa. Heat it to 650℃ and apply a pressure of 50 MPa at the same time, and keep it at that temperature for 1 hour. Then cool it to room temperature with the furnace and demold to obtain a bulk copper material with a high proportion of (111) texture.

[0032] Example 4 Please see Figure 1-3 This embodiment describes a method for the directional controlled preparation of textured copper using graphene, comprising the following steps: 1) Cut commercial pure copper foil to the required size, and ultrasonically clean it in acetone, alcohol and deionized water for 10 minutes in sequence, and then dry it with nitrogen gas for later use.

[0033] 2) Place the cleaned copper foil in a tube furnace, evacuate the furnace, and then introduce a mixture of Ar and H2 gas (H2 flow rate 50 ml / min, Ar flow rate 200 ml / min). Proceed to 1000℃ within 40 minutes. Hold at this temperature for 30 minutes for annealing.

[0034] 3) After annealing, CH4 gas (flow rate 20 ml / min) was introduced and a trace amount of O2 (flow rate 0.5 ml / min) was introduced. The reaction time was 40 minutes. Then, the mixture was naturally cooled to room temperature under Ar atmosphere protection to obtain a single-layer copper-graphene composite material. During this stage, the preferential growth of graphene induced the copper matrix to form a strong (111) texture.

[0035] 4) Stack the single-layer composite materials prepared in step 3) neatly and place them in a hot press mold. Place the mold in a vacuum hot press furnace and evacuate to below 10-3 Pa. Heat to 550℃ and apply a pressure of 50 MPa, hold for 1 hour, then cool to room temperature with the furnace. Demold to obtain a bulk copper material with a high proportion of (111) texture.

[0036] In summary, these four examples systematically verified the effectiveness of the preparation method by adjusting the key variable of hot-pressing sintering temperature, and revealed the influence of process parameters on the final material properties. A detailed summary is as follows: 1. The feasibility of the preparation method was verified. All four examples successfully prepared dense textured copper materials, demonstrating that by using graphene as an inducing layer, combined with chemical vapor deposition (CVD) and hot pressing sintering processes, it is indeed possible to achieve the directional alignment of copper grains and obtain copper materials with specific texture structures.

[0037] 2. The effect of temperature on texture strength was revealed. The comparison of the examples shows that the hot pressing sintering temperature is the key factor that determines the strength of the (111) texture.

[0038] A suitable temperature (such as 750°C in Example 1) is conducive to the full directional migration and rearrangement of copper atoms under the induction of graphene, forming a strong (111) preferred orientation.

[0039] Too low a temperature (e.g., 650°C in Example 3): Insufficient atomic diffusion capacity leads to incomplete recrystallization and weak texture strength.

[0040] Excessively high temperatures (such as 850°C in Example 4): Although atomic diffusion is fast, it may lead to abnormal grain growth or damage to the graphene layer, which is not conducive to the formation of a single texture.

[0041] 3. This confirms that microstructure enhances electrical conductivity. Data from all four embodiments show that the electrical conductivity of the material increases significantly with the increase of (111) texture strength.

[0042] Performance breakthrough: The conductivity of the preferred embodiment (such as embodiment 1) exceeds 100% IACS (International Standard for Annealed Copper), reaching more than 103% IACS.

[0043] Mechanism verification: This directly proves that reducing the number of grain boundaries (especially high-energy grain boundaries) can effectively reduce electron scattering, thereby breaking through the conductivity limit of traditional polycrystalline copper.

[0044] 4. The optimal process window was determined. A comprehensive comparison of the XRD patterns (texture coefficient) and electrical conductivity test data of the four embodiments demonstrates that approximately 750°C is the optimal hot-pressing sintering temperature for this process system. At this temperature, the material can simultaneously achieve the strongest (111) texture and optimal electrical conductivity, realizing the best match between microstructure and macroscopic properties.

[0045] In the attached diagram: Figure 1 The figures show the Raman spectroscopy of copper-graphene prepared at different methane flow rates. As can be seen from the figures, the graphene content increases with the increase of methane flow rate. Excessive flux leads to the enhancement of the D and G peaks, indicating that the number of graphene material layers increases, defects increase, and the quality of graphene decreases.

[0046] Figure 2 These are XRD diffraction patterns of textured copper prepared at different hot-pressing temperatures in the embodiments of the present invention. As the hot-pressing temperature increases, the intensity of the (111) texture gradually increases.

[0047] Figure 3The images show the EBSD (electron backscatter diffraction) orientation patterns of textured copper prepared at different hot-pressing temperatures in this embodiment of the invention. The trend of these patterns is consistent with the XRD diffraction patterns. The results show that the intensity of the (111) crystal plane diffraction peak of the textured copper material prepared in this embodiment is much higher than that of the standard polycrystalline copper powder diffraction pattern, indicating that it has a very strong (111) texture.

[0048] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.

[0049] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for the directional controlled preparation of textured copper using graphene, characterized in that, Includes the following steps: 1) Substrate preparation: The copper foil is cleaned and dried to remove surface oil and oxides; 2) Graphene-induced growth: The treated copper foil is placed in an atmosphere tube furnace and heated to a predetermined temperature under a protective atmosphere; carbon source gas and auxiliary gas are introduced to carry out chemical vapor deposition reaction. During the reaction, the nucleation density, growth rate and coverage area of ​​graphene are precisely controlled by controlling parameters such as the proportion of carbon source gas, reaction time, system pressure and oxygen content, so that the polycrystalline copper foil (111) crystal plane can grow initially and form a textured growth template. 3) Texture growth: The single-layer copper-graphene composite material obtained in step 2) is stacked and hot-pressed under vacuum or protective atmosphere to achieve metallurgical bonding between layers. During the hot pressing process, the hexagonal structure of graphene will stabilize the (111) crystal plane. Its strong interfacial coupling with the copper matrix induces the copper grains to undergo directional recrystallization, causing other crystal planes of the polycrystalline copper foil to transform into the (111) crystal plane during the recrystallization process, forming a copper-graphene composite structure with strong (111) texture, and finally obtaining a dense bulk textured copper material with strong (111) texture.

2. The method for directionally controlled preparation of textured copper using graphene according to claim 1, characterized in that: During the preparation process, the material grains exhibit a preferred orientation.

3. The method for directionally controlled preparation of textured copper using graphene according to claim 1, characterized in that: In step 2), the nucleation density and grain size of graphene are controlled by controlling the CH4 ratio and reaction time, thereby reducing the hot pressing conditions.

4. The method for directionally controlled preparation of textured copper using graphene according to claim 1, characterized in that: In step 3), the hot pressing temperature is 600℃-950℃, the pressure is 30-80MPa, and the holding time is 30-120min.

5. The method for directionally controlled preparation of textured copper using graphene according to claim 1, characterized in that: In step 2), the temperature of chemical vapor deposition is 900℃-1050℃, the carbon source gas is methane (CH4), and its flow rate accounts for 0.1%-5% of the total gas flow rate.

6. The method for directionally controlled preparation of textured copper using graphene according to claim 1, characterized in that: In step 2), a trace amount of oxygen or an oxygen-containing precursor is introduced while the carbon source gas is introduced to regulate the interaction between the graphene edge and the copper substrate and promote the unidirectional growth of graphene.

7. The method for directionally controlled preparation of textured copper using graphene according to claim 1, characterized in that: In step 2), the protective atmosphere is a mixture of argon (Ar) and hydrogen (H2), wherein the hydrogen flow rate is 50 ml / min and the argon flow rate is 200 ml / min.

8. The method for directionally controlled preparation of textured copper using graphene according to claim 1, characterized in that: The preferred temperature for hot pressing sintering is 650℃-850℃, the pressure is 50MPa, and the holding time is 60min.

9. The method for directionally controlled preparation of textured copper using graphene according to claim 1, characterized in that: In the X-ray diffraction (XRD) pattern of textured copper materials with preferred orientation, the diffraction peak intensity of the copper (111) crystal plane is higher than that of the standard polycrystalline copper powder diffraction pattern, and electron backscatter diffraction shows that the grain orientation is highly consistent.